Wawasan Al-Qur’an tentang Keadilan Fiskal: Relevansi Ayat-Ayat Makroekonomi Islam terhadap Pengentasan Kemiskinan: Quranic Insights on Fiscal Justice: The Relevance of Islamic Macroeconomic Verses to Poverty Alleviation - Fatchul Muin, Tri Subegti; Achmad Abubakar; Muhsin Mahfudz (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, IndonesiaInstitut Agama Islam STIBA Makassar, Indonesia, 2025)
Poverty is a structural problem rooted not only in economic inequality but also in the failure of conventional fiscal systems to achieve distributive justice. The Qur’an provides theological and normative insights into fiscal justice, emphasizing the balance between individual ownership rights and collective social responsibility. This study aims to explore the relevance of Qur’anic verses concerning economic justice and wealth distribution in alleviating poverty within the framework of Islamic macroeconomics. The research employs a library-based qualitative method using a thematic tafsir (maudhu‘i) and a normative-descriptive analysis of Qur’anic concepts such as al-‘adl (justice), al-qisṭ (equity), al-infaq (spending), and prohibitions against al-israf (extravagance) and al-bukhl (miserliness). The findings reveal that fiscal justice in the Qur’anic perspective functions not only as an economic mechanism but also as a spiritual instrument to achieve social welfare (al-falah al-ijtima‘i). This perspective provides a conceptual foundation for formulating contemporary Islamic fiscal policies aimed at equity and community empowerment. The study contributes to the development of Islamic economic epistemology by integrating Qur’anic theological values into modern macroeconomic frameworks.